Visual Impairment in Patients with Vernal Keratoconjunctivitis - Khan, Awais Ahmad; Ali, Zulfiqar (Biological and Clinical Sciences Research Journal, 2025)
Vernal Keratoconjunctivitis (VKC) is a chronic, recurrent allergic disorder of the ocular surface that predominantly affects children and young adults in warm climates. The disease can lead to corneal complications and permanent visual impairment if inadequately managed. Despite its clinical importance, there is limited data from Pakistan regarding the magnitude and determinants of VKC-associated vision loss. Objective: To determine the frequency and pattern of visual impairment among patients diagnosed with VKC and to assess its association with demographic and clinical factors in a tertiary care hospital of Pakistan. Methods: This descriptive cross-sectional study was conducted at the Department of Ophthalmology, Ayub Teaching Hospital, Abbottabad, from December 2024 to April 2025. A total of 110 clinically diagnosed VKC patients aged 5–50 years were enrolled using a non-probability consecutive sampling technique. Visual acuity was measured using Snellen's chart and classified according to WHO criteria. Detailed ocular examinations were performed to identify corneal complications, including punctate epithelial erosions, shield ulcers, scarring, and keratoconus. Data were analyzed using SPSS version 20, applying Chi-square and Fisher's exact tests; p-values <0.05 were considered statistically significant. Results: The mean age of participants was 15.6 ± 5.8 years, with a male predominance (70%). Most patients were students (73.6%) and resided in urban areas (59.1%). The most common symptoms were itching (100%), redness (94.5%), and foreign body sensation (80.9%). Mixed-type VKC was the most prevalent subtype (51.8%), followed by palpebral (28.2%) and limbal (20.0%). Corneal involvement was observed in 39.1% of patients, with punctate epithelial erosions (20.0%) being the most frequent complication. Visual impairment was present in 36 (32.7%) patients—mild in 16.4%, moderate in 12.7%, and severe in 3.6%. Visual impairment was significantly associated with corneal complications (p = 0.003), male gender (p = 0.021), and low socioeconomic status (p = 0.045). Conclusion: Nearly one-third of VKC patients exhibited visual impairment, predominantly males and those from lower socioeconomic groups. Corneal involvement, particularly erosions and shield ulcers, was the primary determinant of reduced vision. Early recognition and prompt management of VKC, along with public awareness and regular ophthalmic follow-up, are crucial to prevent irreversible visual disability among affected children in Pakistan.